(untitled) (Research, Society and Development, 2023)
The purpose was to build and validate the content of illustrative material to advise family members and educators of children who stutter. Study with a methodological approach, following the steps recommended in the literature for the validation of educational material. Three groups of judges were selected: eight speech therapists, 10 early childhood educators and 10 family members of stuttering children and adolescents. The judges answered a self-administered questionnaire to judge the content, language, illustrations, layout and motivation of the materials. And, after reading the folder, they should mark one of the levels of agreement (Likert scale): (1) strongly disagree, (2) disagree, (3) neither disagree nor agree, (4) agree, (5) strongly agree, and then three dichotomous questions (yes/no) associated with a space for comments/ suggestions. After organizing and categorizing the data, the Content Validity Index (CVI) was applied to measure the degree of agreement between the judges with the cut-off point of >0.78. Adjustments were necessary in the illustration and layout categories (<0.78). Individual judges’ suggestions and comments involving content and language were considered. The final version in A4 sheet, landscape mode and with three tabs, arranged as follows: cover, back cover with incidence and types (developmental, neurogenic and psychogenic), diagnosis and treatment, favorable attitudes and a reminder about stuttering bullying, in addition to the definition and main manifestations of stuttering. The material was constructed and its content validated, showing a high level of acceptance and agreement among the judges, being a support for health and education professionals and parents about the theme of stuttering. The next stage of the study contemplates the determination of the psychometric properties of the material, in order to validate the items and make it completely validated.